PENYULUHAN TENTANG KANKER SERVIKS DAN PEMERIKSAAN IVA DI DESA JOMBOR, KEC. TUNTANG, KAB. SEMARANG - Dary; Natijati, Arum; Manafe, Meriyanti A.; Amahoru, Cherlin Prissilia; Sopacua, Siendy Clara; Sarupy, Wanda; Zefania, Virara; Gobuino, Yuliana Susanti; Tauho, Kristiani Desimina; Tampubolon, Rifatolistia (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2024)
Cervical cancer is the second highest type of cancer after breast cancer that causes death in women. One of the factors causing the high incidence of cervical cancer in women is the low coverage of early detection of cervical cancer due to a lack of information in the community. This community service activity aimed to provide education about cervical cancer and VIA examinations (Visual Inspection with Acetic Acid). The method used in this health education was the lecture and question-and-answer method supported by leaflets and pictures. The participants for this community service activity were 40 women of Family Welfare Programme in Jombor Village, Tuntang District, Semarang Regency. The results of this community service showed an increase theirs' knowledge about the signs, symptoms, and factors causing cervical cancer, as well as VIA examinations, demonstrated by comparing pre-test and post-test scores. The activities ran well, and participants could understand the given materials.